2021
DOI: 10.1093/jee/toab071
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Termite Locomotion and Allogrooming in Response to Infection by Pathogenic Fungi

Abstract: Termites, being vulnerable to parasitic or pathogenic infections due to large number of individuals living together in colonies, have evolved various behavioral and physiological tactics to resist the infections by those pathogens. Locomotion can help termites collect information on parasites and accordingly exhibit hygienic behaviors. Termites inevitably encounter entomopathogenic fungi during nesting and foraging. However, how these fungal pathogens influence locomotion of termites and how hygienic behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Any decrease in mosquito lifespan can reduce the average number of blood meals consumed, and any reduction in the number of blood meals consumed can decrease the likelihood of the vector acquiring a disease agent and spreading it to new hosts 11 . The entomopathogenic fungus M. anisopliae is known for its virulence against a number of insect species including mosquitoes 11, 46 and termites 41, 47 . Our survival assay results revealed a significant reduction in mosquito survival after application of medium and high concentrations of fungal conidia.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Any decrease in mosquito lifespan can reduce the average number of blood meals consumed, and any reduction in the number of blood meals consumed can decrease the likelihood of the vector acquiring a disease agent and spreading it to new hosts 11 . The entomopathogenic fungus M. anisopliae is known for its virulence against a number of insect species including mosquitoes 11, 46 and termites 41, 47 . Our survival assay results revealed a significant reduction in mosquito survival after application of medium and high concentrations of fungal conidia.…”
Section: Discussionmentioning
confidence: 74%
“…11 The entomopathogenic fungus M. anisopliae is known for its virulence against a number of insect species including mosquitoes 11,46 and termites. 41,47 Our survival assay results revealed a significant reduction in mosquito survival after application of medium and high concentrations of fungal conidia. A previous study involving the exposure of the adult Ae.…”
Section: Discussionmentioning
confidence: 87%
“…This is contrary to Hassan, Huang, Xu, et al (2021), who found in R. chinensis Snyder that the locomotion rates of both male and female dealates were significantly higher than soldiers and workers after injection with Phosphofructokinase dsRNA. The same study also found that locomotion rate variation was dose‐dependent: lower concentrations of M. anisopliae increased termite locomotion, whereas higher concentrations resulted in both decreased locomotion and survival (Hassan, Huang, Mehmood, et al, 2021). Decreased velocity and total distance moved by fungal‐infected queens may therefore be linked to the potential benefits of receiving increased grooming from workers in the future.…”
Section: Discussionmentioning
confidence: 83%
“…Co‐application of AKH with pathogens could yet further enhance these effects by interfering with the immune response in some insect species (Adamo et al, 2008; Gautam et al, 2020; Ibrahim et al, 2017; Ibrahim et al, 2018), potentially making them more susceptible to pathogen‐mediated control, which in termites has proven difficult to implement, in part due to their social immune defence traits, which prevent the spread of infectious disease (He et al, 2018; Davis et al, 2018; Liu et al, 2019; Hassan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%